CHITOSANPOTENTIAL FROM THE GOLD SNAIL SHELL (Pamacea canaliculata) - Febrigusni, Audia; Sukmiwati, Mery; Karnila, Rahman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACT               A waste of gold snail shell in Batusangkar is a type of fishery waste whose processing hasn’t been maximized that still causes a lot of environmental issues. It was a raw material for the production of chitosan. This study aimed to determine the quality of chitosan from gold snail shells. The production of chitosan was carried out with 3 processes, namely: demineralization, deproteination, and deacetylation. The deacetylation degree test was carried out using the FTIR spectroscopy method. The test parameters observed were water content, ash, protein, degree of deacetylation. The results of the research on chitosan obtained water content, ash content and degrees of deacetylation at a temperature concentration of 100oC was 1.48%, 8.67%, and 69.9%, at a temperature of 110oC 2.06%, 8.51 %, and the degree of deacetylation was 54.3%, and at a temperature of 90oC was 1.37%, 8.79%. and the degree of deacetylation was 50.7%. Keywords: Were water content, ash, protein, and degree of deacetylation